The constitutional right to freedom of movement: experience of implementation in the Russian Federation, the Republic of Belarus and the Republic of Kazakhstan - Andrichenko, Ludmila V.; Maslovskaya, Tatiana S.; Musilimova, Karlygash S.; Plyugina, Inna V. (Journal of the Belarusian State University. Law, 2026)
The right to freedom of movement, a fundamental human and civil right, is reflected in the catalog of constitutional values in many modern states. Its nature has been the subject of scholarly research for centuries: legal scholars have explored the essence and content of this right, substantiated the permissible limits of its limitations, and analysed its impact on the exercise of other constitutional rights and freedoms. Today, the right to freedom of movement is primarily considered in the context of regulating migration processes, in conjunction with the principle of state sovereignty. The search for an optimal balance between public and private interests, as well as the interests of foreign citizens and the host society, continues. This article examines the right to freedom of movement from a constitutional and legal perspective, focusing primarily on the legislation of three states (the Republic of Belarus, the Republic of Kazakhstan, and the Russian Federation) all of which enjoy close integration ties. The article examines approaches provided in national legislation to establishing restrictions and prohibitions on this right, providing opportunities for family reunification, and other aspects. General «markers» of legal development include the promotion of the idea of «digital migration», the strengthening of state control (oversight), including through the introduction of new technologies, and the use of a flexible approach to determining the conditions and procedures for entry and stay of various categories of foreign citizens.